Influence of altered solvent environment on the functionality of pigeonpea (Cajanus cajan) and cowpea (Vigna unguiculata) protein isolates - Mwasaru, Mwanjala A.; Muhammad, Kharidah; Bakar, Jamilah; Che Man, Yaakob B. (Elsevier Science, 2000)
Functional properties of pigeonpea and cowpea isolates were determined as a function of pH and NaCl concentrations. At low pH, nitrogen solubility decreased with increasing NaCl concentration whereas, at high pH, it increased. Addition of NaCl to the solvent medium resulted in a marginal improvement and a significant improvement, in the emulsifying activity and emulsion stability of pigeonpea isolate, respectively. The above treatment decreased these properties for the cowpea isolate. Varying both the pH and NaCl concentrations resulted in significant improvements in the emulsifying properties of the isolates relative to the control treatment. NaCl concentrations higher than 0.1 M significantly (P < 0.05) increased the expansion of pigeon and cowpea protein- stabilized foams but reduced foam stability, and adjusting pH from 2 to 8 improved foam expansion but decreased foam stability. Varying both the pH and salt concentration had similar effects on the foaming properties of the isolates. The least gelation concentration (LGC) of the isolates decreased with increasing salt concentration. Adjusting the pH to values away from the apparent isoelectric point, elicited similar responses in LGC. In 0.5 M NaCl solution, adjusting the pH to 2, 6 and 8 resulted in significant reductions in LGC relative to the distilled water protein suspensions.